Vascular cytoprotection, autoimmune disease, and premature atherosclerosis - Justin C Mason (Indian Journal of Rheumatology)
A healthy vascular endothelium is critical to health, and interference with endothelial homeostasis disrupts hemostasis, regulation of vascular tone and blood pressure, leukocyte trafficking, angiogenesis and tissue repair. Endothelial injury and apoptosis leads to endothelial dysfunction, which is closely associated with increased generation of reactive oxygen species, reduced endothelial nitric oxide (NO) synthase, increased consumption, and impaired synthesis of NO. Systemic inflammatory diseases including rheumatoid arthritis and systemic lupus erythematosus are associated with endothelial dysfunction, increased aortic stiffness, and accelerated atherogenesis. Premature cardiovascular disease is well-recognized feature of many rheumatic diseases. The cell and molecular mechanisms related to this remain poorly understood. Specific diseases display individual and common attributes that likely influence cardiovascular risk. A key challenge is the development of the means by which those at highest risk can be identified. Likewise, the ability of current therapies to mitigate risk and the identification of novel vasculoprotective therapies represent important areas of research focus. Similarly, close liaison between rheumatologists and cardiologists is essential to minimize the cardiovascular impact on patients and to ensure that patients with rheumatic disease and coexistent coronary heart disease receive appropriate therapy. Identification of safe therapeutic approaches that combine the targeted immunosuppression required, along with comprehensive vascular protection to control the primary disease and prevent secondary complications over the longer term, remains the ultimate challenge.